PERAN KELUARGA TERHADAP PENYEMBUHAN PASIEN SKIZOFRENIA PARANOID DI UNIT RAWAT JALAN BADAN LAYANAN UMUM DAERAH RUMAH SAKIT JIWA ACEH - Fakhrul Rizal; Mohammad Hendro Muttaqin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Schizophrenia is a complex disorder syndrome that can cause damaging effects on the lives of patients and their family members so that the role of the family is needed for healing an control the symptoms. The prevalence of schizoprhenia patiens in the world there is about0,2%-1,5% and prevalence in this country is about 0,3-1%. The aims in this study is to determine the role of the family in the recovery of patients with schizophrenia paranoid at polyclinic of Mental Hospital in Province of Aceh. This reseach using analytical survey methods by accidental sampling technique and enforceable at polyclinic of Mental Hospital in Province of Aceh in June and July 2017. The sample used is 50 people as the sample. The instrument used in the research is questionnaires. The results showed there is a role of family in the recovery of patients who undergo out patient treatment of schizophrenia in the Mental Hospital in Province of Aceh with a majority of 31 people fairly and minimal of symptom or about 62.0 %(p=0,00).Â The conclusion in this research there is a role of family in the recovery of patients who undergo outpatient treatment of schizophrenia paranoid in the Mental Hospital in Province of Aceh.Keywords: Schizophrenia Paranoid,Recovery, The Roleof Family